Chromosomal microarray analysis allows prenatal detection of low level mosaic autosomal aneuploidy. (14th February 2014) - Hall, Georgina K.; Mackie, Fiona L.; Hamilton, Susan; Evans, Alison; McMullan, Dominic J.; Williams, Denise; Allen, Stephanie; Kilby, Mark D.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Mosaic autosomal aneuploidies detected prenatally complicate genetic counselling, despite the presence of relevant ultrasound scan anomalies. Chromosomal microarray analysis is currently reported to detect mosaicism of between 10% and 30% prenatally. What does this study add? Chromosomal microarray analysis is effective in detecting low level mosaic autosomal aneuploidy in a prenatal setting, which traditional methods may fail to detect. This detection of low level mosaicism supports the use of chromosomal microarray analysis in prenatal diagnosis.